Conductive Heat Transfer in Partially Saturated Gas Diffusion Layers with Evaporative Cooling. Issue 3 (1st March 2022) - van Rooij, Sarah; Magnini, Mirco; Mularczyk, Adrian; Xu, Hong; Büchi, Felix N.; Haussener, Sophia
Abstract : Heat transport is an important, though often neglected function of gas diffusion layers (GDLs) of polymer electrolyte membrane fuel cells. Thermal conductivity is a key property, especially in partially water saturated GDLs and when the phase change of water is considered, such as required for evaporative cooling applications. Continuum models require effective transport properties as input, which in this work were determined for different types of dry and partially saturated commercial GDLs (Toray 060 and 120, Freudenberg H23). Three-dimensional microstructures and phase distributions were recorded using X-ray tomographic microscopy, digitalized and used in direct pore-level simulations. The governing energy conservation equation was solved in the three phases (gas, liquid, solid) with interfacial heat transfer between the phases to determine the effective thermal conductivity. Correlations for through-plane effective thermal conductivity in the different GDL types as a function of saturation are provided. An energy sink term, accounting for the evaporation of water, was added, enabling a quantification of the effective conductive heat transfer in GDLs with evaporative cooling. The water distribution (clustered or layered) in the GDLs was found to be a key factor for the thermal conduction and evaporative cooling ability.